Risk assessment of IT governance: a systematic literature review - Che Pa, Noraini; Anthony Jnr, Bokolo; Nor, Rozi Nor Haizan; Azmi Murad, Masrah Azrifah (Asian Research Publication Network, 2015)
Risk assessment (RA) is one of the main activities in risk management of IT governance. Basically, IT governance is a process or a procedure that involves evaluating and directing the plans for the use of ICT to support the organization and monitoring the achievement of these plans. The risks that may emerge during the implementation of IT governance must be properly assessed to ensure its success. In general, risk assessment in IT governance is focusing on the essential process to aid all relevant parties involved in IT implementation from both the technical and services aspects. Many studies related to IT risk assessment and risk assessments of IT governance have been reviewed based on a systematic method which is called Systematic Literature Review (SLR). Based on this approach, all previous studies related to this title can be analyzed systematically. Based on the same framework, this paper presents the results of the systematic reviews on the concept, process, framework, model and challenges of risk assessment of IT governance. In general, the findings from this review indicate that RA requires a more holistic consideration on numerous limitations and issues.